A Complex Character of the Civil War in Yemen: A Perspective from Pakistan - Khurshid Khan; Dr Fouzia Amin; Raza Muhammad (National University of Modern Languages (NUML), Islamabad, 2023)
The civil war in Yemen is a puzzling case, involving local, regional and global actors with conflicting motives. Till recent past, Yemen had not been a hotbed for sectarian strife yet, in the milieu of the 'Gulf War-2003' followed by the 'Arab Spring', the ground realities greatly changed, bringing 'sectarian divide' as one of the many dimensions in the conflict. While Iran continues to deny Saudi accusations of its great designs in Middle East, still we need to ascertain the facts by probing the complex interplay between drivers and actors placed at various levels. The study concludes that besides the 'sectarian divide', there are other dimensions of the conflict which are grounded on political, social and strategic aspects, directly influenced by the outside players. As a part of the real politick, Iran and Saudi Arabia are striving to have their grip over the Middle East including the Yemen. The study also concludes that the Yemen being its soft underbelly, Saudi Kingdom would not compromise on its stated goals of having direct influence over it, even if it has to pay a heavy cost. The study suggests that to realize a durable peace in the region, Iran and Saudi led coalition should bridge trust deficit, address perception problems and help various factions to resolve their differences by signing a 'new social contract'. From theoretical angle, this paper adopts a realist line, focusing on security concerns of the state actors.